An exploration of the mourning rituals of the people of Bethal in the Mpumalanga Province of South Africa - Mamosadi, Kedeboni Precious (My University, 2023)
People from diverse cultures have unique ways of conceptualising and responding to death through varying degrees of mourning and grieving processes. This study is centred on exploring the traditional mourning rituals of African indigenous people with reference to the people of Bethal, in the Mpumalanga Province, South Africa. The study adopted a qualitative research methodology, with critical phenomenology as a research approach. The participants were the residents of Bethal, a small, under resourced township in the Govan Mbeki District, Mpumalanga Province. Eight in-depth, semi structured, face to face interviews were conducted, recorded and transcribed verbatim; and analysed through Thematic Analysis. Sampling procedure followed a purposive strategy while this cohort of people were selected according to their willingness to participate, their availability and being permanent residents of this area. The study found that mourning can be an individualised and collective experience. The study further describes how African people inherently ascribe to certain traditional mourning rituals in order to deal with the loss of a loved one. Findings contribute to existing research on African ways of grieving by highlighting grief and mourning rituals through an African lens embedded in the subjective narratives of the participants. Results from this study further demonstrate how Covid19 restrictions have affected these traditional mourning rituals. Finally, recommendations are provided on how African people can realign their mental healthcare, while preserving their cultural mourning rituals.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts by coursework and Research Report in the field of Psychology to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2023